A knowledge-based retrofit priority identification framework of the mineral processing to assist in process improvement - Furong Sun; Dakuo He; Hongying Lin; Qiang Li; Chun Wang; Jiacheng Liu; Duanduan Wang (Minerals Engineering, 2026)

Unlocking collagen-derived novel antioxidant peptides from by-product bones of silver carp: label-free peptidomic discovery, bioinformatics-aided mechanistic elucidation, and cytoprotective effects against oxidative damage - Jin Zhang; Feng Lin; Yimeng Mei; Ruoyu Xie; Jiaxin Chen; Jun Hu; Hongying Du; Guijie Hao; Shuangxi Li; Wenxuan Chen (Food Research International, 2026)

Online proteolysis and specific affinity enrichment of ACE inhibitory peptides on a magnetic nanoplatform from Torreya grandis protein - Kexin Liu; Jiajun Cui; Ke Xu; Jiaqi Zheng; Yixuan Xiao; Lin Chen; Sha Li; Jiyou Yang; Hongying Guo; Xin Wang; Fei Gao; Jie Li; et al. (Food Chemistry, 2026)

The properties and effects of suspended matter in zinc electrowinning - Zhanpeng Chen; Liang Zhou; Leicheng Shi; Guo Lin; Hongying Xia; Linqing Dai; Libo Zhang (Hydrometallurgy, 2026)

A cyclic ecological strategy for ameliorating saline-alkali soils using biochar and Cenchrus fungigraminus (JUJUNCAO) - Shaojuan Yan; Lingyi Hu; Jian Ma; Lihuai Ma; Dongmei Lin; Hongying Sun (Environmental Research, 2026)

Development of multifunctional intelligent packaging based on plasma-modified starch and triple-crosslinked anthocyanin nanocomplexes for salmon preservation and freshness monitoring - Fanglei Zou; Miao Yang; Lin Chen; Daoyi Song; Junhua Wu; Wei Wang; Hongying Wang (Chemical Engineering Journal, 2026)

Molecular characterization of a novel partitivirus from quinoa (Chenopodium quinoa) in China - Wenqi Mao; Jiajia Lin; Zhongtian Xu; Penghuan Rui; Xinxin Fang; Hongying Zheng; Yuwen Lu; Jianping Chen; Fei Yan; Guanwei Wu (Archives of Virology, 2026)

A new insight of size-dependent plastics particles kinetics with regarding of metabolomics effects in liver and kidney - Hongying Gao; Jing Li; Zehua Xu; Yiyang Duan; Bowen Su; Mengting Li; Banyun Zheng; Miaomiao Ren; Hao Chang; Heng Wang; Yi Lin; Heqing Shen (Environmental Pollution, 2025)

Determinants and dynamic mechanisms of microbial communities in mangrove sediments of the qingjiang estuary - Yongjun Luo; Siyue Zhao; Qingbi Tan; Hongying Guo; Jianliang Lin; Huafeng Chen; Jiange Jiao; Hui Nie; Saihua Huang; Lixia Niu (Plant and Soil, 2025)

Enhancing cyclodextrin glycosyltransferase-mediated potato starch modification via plasma-activated water and twin-screw extrusion treatment - Fanglei Zou; Hongyun Hao; Miao Yang; Chunming Tan; Lin Chen; Junhua Wu; Hongying Wang (Food Chemistry, 2025)

Synergistic 3D network eengineering and surface terminal regulation in MXene/graphene aerogels with ultrahigh volumetric capacitance and rate-capability for supercapacitors - Hongying Zhao; Hailong Shen; Man Cai; Jiaheng Xu; Lin Li; Siyi Liu; Shuaikai Xu; Xianqing Liang; Wenzheng Zhou; Jin Guo; Haifu Huang; Ming Li (Chemical Engineering Journal, 2025)

Energy poverty and household consumption upgrading: evidence from the China family panel studies - Hongying Lin; Ya-Lan Liu (Environment, Development and Sustainability, 2025)

Assessing the effect of perfluoroalkyl and polyfluoroalkyl substances on cardiovascular-kidney-metabolic syndrome: Insights from an interpretable machine learning model - Zidan Zheng; Yuyan Xu; Ning Kang; Yiwen Dong; Xin Wang; Lin Zhang; Hongying Bian; Qibing Zeng (Science of The Total Environment, 2025)

Glandular trichome heads confer cadmium tolerance in Nicotiana tabacum L. via the co-regulation of JA and ABA signaling - Shuai Wang; Hong Cui; Yong Lin; Shiqiang Zhang; Yue Li; Meiqi Yan; Qi Wang; Chaoyi Zhou; Hongying Zhang (Journal of Hazardous Materials, 2025)

Joint technique “parallel peptide synthesis & de novo sequencing” development for the structure verification and high-throughput activity screening of biological peptides from sea cucumber (Stichopus japonicus) intestinal hydrolysate - Yimeng Li; Shengfang Gao; Xiaohui Zhang; Zhuo Cao; Youyou Guo; Runkun Zhao; Yonggang Liu; Xinxin Li; Hongying Lin; Qi Qin; Bingqing Yi; Guodong Zhao (Food Research International, 2025)

Oxidation extraction of copper from chalcopyrite powered by ultrasound enhanced free radical mechanism - Zhuoyu Yin; Dekun Zhang; Lun-Ao Ouyang; Likang Fu; Yonggang Zuo; Shixing Wang; Gengwei Zhang; Guo Lin; Hongying Xia; Libo Zhang (Process Safety and Environmental Protection, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Paleoclimate Fluctuations Facilitate the Biogeographical History of Endemic Species of Freshwater Crabs in China via Cycles of Introgressive Hybridisation and Habitat Isolation - Boyang Shi; Ruxiao Wang; Danhong Song; Juanjuan Xu; Lin Zhu; Yufang Sun; Rui Hu; Neil Cumberlidge; Da Pan; Hongying Sun (Journal of Biogeography, 2025)
Aim The impact of Pleistocene climate fluctuations on the biogeographical history of aquatic species has been a topic of enduring debate. This issue poses particular challenges for parapatric closely related species, especially those situated in transition zones where species assemblages occur between distinct zoogeographic boundaries. Location Eastern China. Taxon Five closely related Sinopotamon species and subspecies, S. shensiense , S. honanense , S. y. yangtsekiense , S. y. shanxianense , and S. y. tongbaiense . Methods These parapatric Sinopotamon species and subspecies, distributed along the boundary between the Palaearctic and Oriental realms in eastern China, offer an ideal model for addressing these challenges. We explored the biogeographic history of these species by conducting a comparative phylogeographic analysis using nine microsatellite loci and two mitochondrial DNA sequences, combined with morphological variation and fine‐tuned ecological niche modelling. Results Our phylogeographic analyses consistently revealed two well‐supported clades: clade A, for S. y. yangtsekiense , and clade B, which includes other species showing polyphyletic patterning and significant gene introgression. The Nanyang Basin and surrounding mountains regions (NBSM) was identified as a critical shared refuge and hybrid zone, facilitating interspecific introgression through at least two putative hybridisation events. During the Late Pleistocene glacial cycles, introgressive hybridisation of these species occurred in the NBSM, followed by rapid expansion and colonisation of heterogenous habitats during interglacial cycles, with dispersal corridors largely aligning with the local river system. In particular, the diffusion corridor of S. honanense significantly disrupted the continuous distribution of S. y. shanxianense and S. y. tongbaiense , indicating that S. honanense has replaced S. y. shanxianense and S. y. tongbaiense in the NYSM and caused a disruption in its distribution. Main Conclusions The biogeographic histories of the species in clade B are consistent with a mixing–isolation–mixing model, which suggests that populations experienced repeated introgressive hybridisation during glacial periods and regional habitat isolation during interglacial periods. Our findings represent a classic case of fine tracking biogeographical scenarios in parapatric species and provide unprecedented insights into the evolutionary radiation of the freshwater fauna that occupies zoogeographic boundaries.

Exosomal miRNA reprogramming in pyroptotic macrophage drives silica-induced fibroblast-to-myofibroblast transition and pulmonary fibrosis - Lin Zhang; Jiaqi Tian; Ning Li; Yongheng Wang; Yulan Jin; Hongying Bian; Min Xiong; Zitong Zhang; Jiahua Meng; Zhengpu Han; Shuyin Duan (Journal of Hazardous Materials, 2025)

Gestational exposure to carbon black nanoparticles triggered fetal growth restriction in mice: The mediation of inactivating autophagy-lysosomal degradation system in placental ferroptosis - Jing Li; Hongying Gao; Zehua Xu; Biling Gao; Liang Zhang; Bowen Su; Shijing Yang; Jiangling Liu; Ya Liu; Xiuxiu Wang; Heng Wang; Yi Lin; et al. (Science of The Total Environment, 2025)

Correction to: Effects of an intraoperative intravenous Bolus Dose of Dexmedetomidine on postoperative catheter-related bladder discomfort in male patients undergoing transurethral resection of bladder tumors: a randomized, double-blind, controlled trial - Tianhua Zhang; Huiting Li; Chunnan Lin; Rui An; Wenqian Lin; Hongying Tan; Longhui Cao (European Journal of Clinical Pharmacology, 2025)

Modeling virus-stimulated proliferation of CD4 + T-cell, cell-to-cell transmission and viral loss in HIV infection dynamics - Jiawei Deng; Hongying Shu; Lin Wang; Xingfu Zou (Mathematical Biosciences, 2024)

Cryopreservation-enhanced differentiation capacity of embryogenic cultures of Castanea mollissima - Shuangxian Liu; Liang Lin; Biao Han; Junchao Ma; Hugh W. Pritchard; Xiaojian Hu; Min Deng; Hongying Chen (Cryobiology, 2024)

The impacts of forest resources, green investment, healthcare, and education on environmental pollution: China Carbon neutrality program - Donghai Huang; Huajie Shen; Yuan Miao; Rongfeng Ding; Yang Lin; Hongying Tan (Journal of Cleaner Production, 2024)

Detection of Turbulence Anomalies Using a Symbolic Classifier Algorithm in Airborne Quick Access Record (QAR) Data Analysis - Zibo Zhuang; Kunyun Lin; Hongying Zhang; Pak-Wai Chan (Advances in Atmospheric Sciences, 2024)

Causal Association of Cytokines and Growth Factors with Stroke and Its Subtypes: a Mendelian Randomization Study - Gengbin Chen; Tuo Lin; Manfeng Wu; Guiyuan Cai; Cheng Wu; Qian Ding; Jiayue Xu; Hongying Chen; Wanqi Li; Guangqing Xu; Yue Lan (Molecular Neurobiology, 2024)

Identification and quantification of microplastics in salts by complementary approaches using pyrolysis-gas chromatography/quadrupole-time of flight mass spectrometry (Py-GC/QTOFMS) and laser direct infrared (LDIR) chemical imaging analysis - Hongying Gao; Heng Wang; Yuchao Wang; Yi Lin; Jianbo Yan; Heqing Shen (Environmental Pollution, 2024)

Anti-CD20 treatment attenuates Th2 cell responses: implications for the role of lung follicular mature B cells in the asthmatic mice - Jilong He; Jingling Li; Qibin Lin; Haiyang Ni; Sisi Huang; Hong Cheng; Xuhong Ding; Yi Huang; Hongying Yu; Yaqing Xu; Hanxiang Nie (Inflammation Research, 2024)

Effects of an intraoperative intravenous Bolus Dose of Dexmedetomidine on postoperative catheter-related bladder discomfort in male patients undergoing transurethral resection of bladder tumors: a randomized, double-blind, controlled trial - Tianhua Zhang; Huiting Li; Chunnan Lin; Rui An; Wenqian Lin; Hongying Tan; Longhui Cao (European Journal of Clinical Pharmacology, 2024)

Complete genome sequence of Paris polyphylla chlorotic mottle virus infecting Paris polyphylla var. yunnanensis in southwest China - Qiongji He; Binghua Chen; Hongying Zheng; Yuhao Cao; Mengyin Hua; Yueyan Yin; Jiejun Peng; Junmin Li; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2023)

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

Complete genome sequence of a novel mitovirus detected in Colocasia esculenta - Mengting Wu; Chanchan Huang; Lin Wang; Bin Ke; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2023)

Konjac glucomannan/low-acyl gellan gum edible coating containing thymol microcapsule regulates cell wall polysaccharides disassembly and delays postharvest softening of blueberries - Peng Huang; Jie Ding; Chunyan Liu; Hongying Li; Chenlin Wang; Yezi Lin; Dur E. Sameen; Md Alomgir Hossen; Mingrui Chen; Jing Yan; Yaowen Liu; Wen Qin (Postharvest Biology and Technology, 2023)

The effects of prenatal PM2.5 oxidative potential exposure on feto-placental vascular resistance and fetal weight: A repeated-measures study - Weiwei Lin; Yuming Lai; Shuling Zhuang; Qiannan Wei; Hedi Zhang; Qiansheng Hu; Peng Cheng; Manman Zhang; Yuhong Zhai; Qingqing Wang; Zhenyan Han; Hongying Hou (Environmental Research, 2023)

Irisin protects against doxorubicin-induced cardiotoxicity by improving AMPK-Nrf2 dependent mitochondrial fusion and strengthening endogenous anti-oxidant defense mechanisms - Caili Zhuo; Juanjuan Xin; Wenjing Huang; Die Zhang; Xin Yan; Ruli Li; He Li; Jie Lan; Lan Lin; Lingyu Li; Xuemei Wang; Linling Liu; et al. (Toxicology, 2023)

Bifunctional reduced graphene oxide/polyelectrolyte/NiFe layered double hydroxide composites for efficient catalyzed dephosphorylation and 4-nitrophenol reduction - Zijun Xie; Bo Sun; Hongying Lin; Meng Fu; Yi Zhang; Zequn Ma; Xiangming Li (Journal of Water Process Engineering, 2023)

Separation, structural identification and antibacterial activity of pectin oligosaccharides derived from seed melon - Min Gao; Xiaotian Wang; Jiangli Lin; XiaoYing Liu; Danping Qi; Yulu Luo; Yeerken Aheyeli-kai; Hongying Ma (Food Bioscience, 2023)

Enhancing the targeting performance and prolonging the antibacterial effects of clove essential oil liposomes to Campylobacter jejuni by antibody modification - Xiaochen Chen; Hongying Yang; Changzhu Li; Wei Hu; Haiying Cui; Lin Lin (Food Research International, 2023)

Adaption of tobacco rattle virus to its solanaceous hosts is related to the codon usage bias of the hosts and that of the viral 16 K gene - Qi Lin; Yuanting Zheng; Yueyan Yin; Yi Chen; Miaomiao Li; Hongying Zheng; Jianping Chen; Fei Yan; Yuwen Lu; Shengchun Xu (European Journal of Plant Pathology, 2023)

Complete nucleotide sequence of hackberry virus A, a tentative member of the genus Waikavirus - Jiajia Weng; Mengting Wu; Zhuangxin Ye; Lin Wang; Bin Ke; Chanchan Huang; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; et al. (Archives of Virology, 2023)

Effect of Iodine Nutrition Status on Thyroid Function and Pregnancy Outcomes - Hongying Zha; Lin Yu; Yi Tang; Lu Sun; Qingxin Yuan (Biological Trace Element Research, 2023)

Complete genome sequence of iris potyvirus B infecting Lilium lancifolium in China - Qi Lin; Dankan Yan; Mengying Hua; Yueyan Yin; Hongying Zheng; Jianping Chen; Fei Yan; Jiejun Peng; Qiongji He; Yuwen Lu (Archives of Virology, 2022)

Effects of cervicothoracic postures on the stiffness of trapezius muscles - Hongying Liang; Suiqing Yu; Man Hao; Weixin Deng; Ming Lin; Zheng Zhang; Chunlong Liu (Medical & Biological Engineering & Computing, 2022)

Characterization of the trophic transfer and fate of methylmercury in the food web of Zhalong Wetland, Northeastern China - Jinming Luo; Wenchong Zhang; Lin Bai; Hongying Li; Zhongyan Gao (Environmental Science and Pollution Research, 2022)

Expression profiling of WRKY transcription factors in Spinach - Yaying Ma; Shuai Chen; Hongying Yu; Ruoyu Li; Zhicong Lin; Mingxing Cai; Min Tang; Xingtan Zhang; Ray Ming (Euphytica, 2021)

Complete genome sequence of a putative novel ilarvirus isolated from Eleocharis dulcis - Lanqing Lv; Xinyang Wu; Jiajia Weng; Yuchao Lai; Kelei Han; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; et al. (Archives of Virology, 2021)

Construction of an infectious full-length cDNA clone of potato aucuba mosaic virus - Buyang Chen; Qi Lin; Yueyan Yin; Liangliang Jiang; Fang Wang; Shuzhen Hu; Xinyang Wu; Fei Xu; Jiejun Peng; Hongying Zheng; Chengqi Yan; Xiaohan Mo; et al. (Archives of Virology, 2021)

Complete genome sequence of passiflora virus Y infecting passion fruit in China - Binghua Chen; Dali Wu; Hongying Zheng; Guangze Li; Yuhao Cao; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2021)

Complete genome sequence of a novel foveavirus isolated from Allium sativum L. in China - Qi Luo; Shuzhen Hu; Qi Lin; Fei Xu; Jiejun Peng; Hongying Zheng; Guanwei Wu; Shaofei Rao; Jianping Chen; Yuwen Lu; Fengling Guo; Fei Yan (Archives of Virology, 2021)

Complete genome sequence of a new achyranthes virus A isolate from Achyranthes bidentata in China - Xinyang Wu; Yuchao Lai; Lanqing Lv; Kelei Han; Ziqiang Chen; Yuwen Lu; Jiejun Peng; Lin Lin; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2021)

Cloning and expression of a thermostable keratinase gene from Thermoactinomyces sp. YT06 in Escherichia coli and characterization of purified recombinant enzymes - Lin Wang; Ying Zhou; Ying Huang; Qishun Wei; Hongying Huang; Chengbao Guo (World Journal of Microbiology and Biotechnology, 2019)

Cold water immersion test (10 °C, 10 min) for diagnosing vibration-induced white finger among a group of polishers in a subtropical environment - Bin Xiao; Danying Zhang; Maosheng Yan; Hongying Qu; Wei Wen; Xiao Zhang; Hansheng Lin; Ying Ye; Ting Chen; Qingsong Chen (International Archives of Occupational and Environmental Health, 2019)

Nutrient Recovery from Digestate of Anaerobic Digestion of Livestock Manure: a Review - Lin Shi; Walquiria Silva Simplicio; Guangxue Wu; Zhenhu Hu; Hongying Hu; Xinmin Zhan (Current Pollution Reports, 2018)

Histopathological changes in zebrafish embryos exposed to DLPCBs extract from Zhanjiang coastal sediment - Yunpeng Yu; Fanghong Nie; Anthony Hay; Hongying Lin; Yi Ma; Xianghong Ju; Dongliang Gong; Jinjun Chen; Ravi Gooneratne (Environmental Monitoring and Assessment, 2017)

Ordovician intrusive rocks from the eastern Central Asian Orogenic Belt in Northeast China: chronology and implications for bidirectional subduction of the early Palaeozoic Palaeo-Asian Ocean - Hongying Li; Zhiguang Zhou; Pengju Li; Da Zhang; Changfeng Liu; XiaoQi Zhao; Lizhen Chen; Congnan Gu; Tingting Lin; Mengmeng Hu (International Geology Review, 2016)

Development of an agroinoculation system for full-length and GFP-tagged cDNA clones of cucumber green mottle mosaic virus - Hongying Zheng; Caili Xiao; Kelei Han; Jiejun Peng; Lin Lin; Yuwen Lu; Li Xie; Xiaohua Wu; Pei Xu; Guojing Li; Jianping Chen; Fei Yan (Archives of Virology, 2015)

Detection of pepper mild mottle virus in pepper sauce in China - Jiejun Peng; Bingbin Shi; Hongying Zheng; Yuwen Lu; Lin Lin; Tong Jiang; Jianping Chen; Fei Yan (Archives of Virology, 2015)

Intron retention and 3′-UTR analysis of Arabidopsis Dicer-like 2 transcripts - Qiongji He; Jiejun Peng; Fei Yan; Lin Lin; Yuwen Lu; Hongying Zheng; Hairu Chen; Jianping Chen (Molecular Biology Reports, 2012)

Interaction between potyvirus P3 and ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO) of host plants - Lin Lin; Zhaopeng Luo; Fei Yan; Yuwen Lu; Hongying Zheng; Jianping Chen (Virus Genes, 2011)

Mapping the self-interacting domains of TuMV HC-Pro and the subcellular localization of the protein - Hongying Zheng; Fei Yan; Yuwen Lu; Liying Sun; Lin Lin; Li Cai; Mingsheng Hou; Jianping Chen (Virus Genes, 2011)

Molecular cloning and characterization of the Dicer-like 2 gene from Brassica rapa - Fei Yan; Jiejun Peng; Yuwen Lu; Lin Lin; Hongying Zheng; Hairu Chen; Jianping Chen; Michael J. Adams (Molecular Biology Reports, 2009)

Identification of novel splice variants of the Arabidopsis DCL2 gene - Fei Yan; Jiejun Peng; Yuwen Lu; Lin Lin; Hongying Zheng; Hairu Chen; Jianping Chen; Michael J. Adams (Plant Cell Reports, 2009)

A high-density intervarietal map of the wheat genome enriched with markers derived from expressed sequence tags - Shulin Xue; Zhengzhi Zhang; Feng Lin; Zhongxin Kong; Yong Cao; Chunjun Li; Hongying Yi; Mingfeng Mei; Huilan Zhu; Jizhong Wu; Haibin Xu; Dongmei Zhao; et al. (Theoretical and Applied Genetics, 2008)